2013
DOI: 10.1590/1678-775720130010
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and fluoride release capacity of orthodontic bonding materials

Abstract: 6XEPLWWHG -DQXDU\ 0RGL¿FDWLRQ $SULO $FFHSWHG 0D\O EMHFWLYH 7KH DLP RI WKLV VWXG\ ZDV WR HYDOXDWH WKH DQWLPLFURELDO DQG ÀXRULGH UHOHDVLQJ capacity of 3 bonding materials. Material and Methods: Thirty nine specimens with standardized surface smoothness and dimensions were prepared. The antimicrobial capacity of the materials against S. mutans, L. casei and C. albicans was evaluated by determining the percentage of growth inhibition of these microorganisms in an inoculated medium, obtained by optical density read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Thus, a material that is capable of releasing both fluoride and calcium ions would be expected to enhance the formation of caries-resistant fluoroapatite on the surface of the tooth which has been shown to make the major contribution to caries prevention. [36] Given the magnitude of the use of composites as dental restoratives, composites that contain available sources of these ions may have substantial advantages compared to those that do not release these ions. As is evident from Figures 1 and 3, both of the BAG composites in this study were found to release calcium and fluoride ions prior to and following fluoride recharge.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a material that is capable of releasing both fluoride and calcium ions would be expected to enhance the formation of caries-resistant fluoroapatite on the surface of the tooth which has been shown to make the major contribution to caries prevention. [36] Given the magnitude of the use of composites as dental restoratives, composites that contain available sources of these ions may have substantial advantages compared to those that do not release these ions. As is evident from Figures 1 and 3, both of the BAG composites in this study were found to release calcium and fluoride ions prior to and following fluoride recharge.…”
Section: Discussionmentioning
confidence: 99%
“…To standardize the dimensions of the specimens, a prefabricated Teflon matrix with perforations of 5 mm of diameter and 2 mm of thickness was used, as described in a previous study. 7 A single researcher manipulated the materials in accordance with the manufacturers' instructions, and then inserted them into the matrix in a single increment. Both light cure bonding composites (XT and PLUS) were inserted into the matrix directly from their syringe.…”
Section: Preparation Of Specimensmentioning
confidence: 99%
“…studies point out that bonding materials' properties, such as surface roughness and fluoride release, can influence risk of development of caries. 5,6,7,8,9,10,11 An ideal orthodontic bonding material, besides being able to resist unintentional debonding forces, must be biocompatible and maintain its biological, physical and chemical properties under any condition. Due to the complexity of the oral cavity, they must be capable of withstanding salivary biochemistry, constant changes in pH, different temperatures, and particularly the resident oral microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have shown fluoride release from adhesive systems, suggesting that these materials have some effect in the enamel and dentin remineralization process and contribute to the control of secondary caries (2,(13)(14)(15)(16)(17). A previous study evaluated fluoride release behavior and the demineralization inhibition capacity of two adhesive systems and the conclusion was that adhesive systems have a fluoride-releasing behavior as they were able to reduce dental tissue demineralization after acid exposure (8).…”
Section: Introductionmentioning
confidence: 99%